Kepribadian Tokoh Utama Dalam Novel Rembulan Tenggelam Di Wajahmu Karya Tere Liye (Kajian Psikoanalisis Sigmund Freud) - Maftuhah (Jurnal Pendidikan Islam, 2019)
Abstract: This study aimed to describe (1) the personality id figure Rey in the novel "The moon Drowned In Your Face" Work Tere Liye, (2) the personality ego character Rey in the novel "The moon Drowned In Your Face" Work Tere Liye, (3) personality super ego character Rey in his novel "the moon Drowned in Your Face" Tere Liye work. This study was a qualitative descriptive study and included in this type of library research. The data used in this study is novel Rembulan Drowning In Your Face Tere Liye Work, published by Republika Jakarta pata first printing in 2009 and consists of 426 pages. Data collection techniques used in this research is the engineering documentation and observation techniques. Teknk data analysis aims to describe the elements of fact stories that form the main characters' personalities that exist in the novel "The moon Drowned In Your Face" Work Tere Liye ". Based on the analysis, it can be concluded personality of id, ego and super ego that experienced by the main character. Based on the results of the study, that the personality Ray in the novel Rembulan Drowning In Your face has the id that is present in the form of hatred against a dark past, the curiosity over his true identity, as well as the ambition to destroy those he considered duplicity. Ego Ray looked at the rebellion he often did to help the people he loved. Super ego Ray looked at the behavior that always decide things according to his conscience desires.